PVD Ti coating on Sm-Co magnets - Bovda, O.M.; Bovda, V.O.; Chen, C.H.; Garkusha, I.E.; Leonov, S.O.; Onischenko, L.V.; Tereshin, V.I.; Tortika, O.S. (Вопросы атомной науки и техники, 2008)
The combination of conventional ion-plasma deposition (PVD) and pulsed plasma technologies (PPT) has been applied for rare-earth Sm-Co based magnets, to provide them with enhanced corrosion resistance. The influence of pulsed plasma treatment on Sm-Co magnets with deposited titanium PVD coatings has been investigated. It was revealed that thickness of modified layer significantly depends on the thickness of initial titanium film and plasma treatment regimes. As a result of plasma treatment with energy density of 30 J/cm² and pulse duration of ~ 5 μs fine-grained layer with the thickness of 70 microns has been formed on the Sm-Co magnet with pure titanium film of 50 micron. According to SEM analyses considerable diffusion of titanium to the bulk of the magnet, on the depth of 20 microns, took place. Such reaction enhances strong bonding between the coating and the magnet. Традиційна технологія іонно-плазмового нанесення захисних покриттів та технологія імпульсної плазмової обробки було застосовано для покращення корозійної стійкості магнітів на базі сплаву Sm-Co. Досліджено вплив дії імпульсних плазмових потоків на магніти Sm-Cо з попередньо нанесеною титановою плівкою. Встановлено, що товщина модифікованого шару значно залежить від товщини вихідної титанової плівки та режиму плазмової обробки. Після плазмової обробки магніту з попередньо нанесеною титановою плівкою (50 мкм) з густиною плазмового потоку 30 Дж/см² та довжиною імпульсу 5 мкс товщина модифікованого шару складала 70 мкм. За даними електронної мікроскопії було встановлено, що відбувалось суттєва дифузія титану у матеріал магніту на глибину до 20 мкм, що сприяло покращенню зчеплення між магнітом та покриттям. Традиционная технология ионно-плазменного напыления защитных покрытий в сочетании с импульсной плазменной обработкой была использована для улучшения стойкости магнитов на базе сплава Sm-Со. Исследовано влияние импульсных плазменных потоков на магниты Sm-Co c предварительно нанесенным титановым покрытием. Установлено, что толщина модифицированного слоя значительно зависит от толщины исходного титанового покрытия и режима плазменной обработки. После обработки магнита с предварительно нанесенным титановым покрытием 50 мкм, высокоэнергетическими плазменными потоками с плотностью плазменного потока 30 Дж/см² и длительностью импульса 5 мкс толщина модифицированного слоя составляла 70 мкм. По данным электронной микроскопии было установлено, что происходила существенная диффузия титана в материал магнита на глубину до 20 мкм, что способствовало улучшению сцепления между магнитом и покрытием.